2008
DOI: 10.1002/bjs.5982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hospital volume on outcome of pancreaticoduodenectomy in Italy

Abstract: The outcome of PD in Italy is dependent on hospital volume and a policy of centralization may therefore be appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
142
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(153 citation statements)
references
References 32 publications
6
142
2
3
Order By: Relevance
“…Other studies have found an association between higher hospital volume and lower post-operative mortality following surgery for pancreatic cancer. [5][6][7][8][9]21] In the present study the association between hospital procedure volume and survival was strengthened by adjustment for case-mix and resection quintile but it did not reach statistical significance. It is feasible that this study was underpowered since only nine hospitals carried out 30 or more procedures per year in at least one year during the period.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Other studies have found an association between higher hospital volume and lower post-operative mortality following surgery for pancreatic cancer. [5][6][7][8][9]21] In the present study the association between hospital procedure volume and survival was strengthened by adjustment for case-mix and resection quintile but it did not reach statistical significance. It is feasible that this study was underpowered since only nine hospitals carried out 30 or more procedures per year in at least one year during the period.…”
Section: Discussionmentioning
confidence: 68%
“…[5][6][7][8][9][10] Previous studies from our group that focused on oesophageal and gastric cancer [14] and on lung cancer [15] found lower death rates in areas where a higher proportion of patients underwent surgical resection. We also found lower death rates in patients operated in hospitals that carry out a greater number of operations a year despite an adverse case-mix in the higher procedure volume hospitals.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, their contribution is valuable in demonstrating the impact of ERAS. There was no validity in comparing the outcomes from these studies with those focused on colorectal surgery, since PD is a challenging operation with a high rate of complications and a measurable mortality risk even in expert hands (36).…”
Section: Discussionmentioning
confidence: 99%
“…Pooled morbidity, postoperative pancreatic fistula and reoperation rates were similar in the two types of centers as has already been reported in the United States experience. The length of stay was shorter in HVCs than in LVCs as described by Balzano et al [21] for laparotomic pancreatic surgery. Furthermore, the R1 resection rate was similar in HVCs and LVCs.…”
Section: Discussionmentioning
confidence: 80%